Hierarchical Toughening of Nacre‐Like Composites. (8th January 2019) - Grossman, Madeleine; Pivovarov, Dmitriy; Bouville, Florian; Dransfeld, Clemens; Masania, Kunal; Studart, André R.
Abstract: Reinforced polymer‐based composites are attractive lightweight materials for aircrafts, automobiles, and turbine blades, but still show strength and fracture toughness lower than traditional metals. An interesting approach to address this issue is to fabricate composites with structural features that absorb part of the elastic energy stored in the material during fracture through extrinsic and intrinsic toughening mechanisms behind and ahead of the crack tip, respectively. Inspired by the nacreous layer of mollusk shells, the fracture behavior of multiscale composites that combine intrinsic toughness from a brick‐and‐mortar structure connected through nanoscale mineral bridges and extrinsic toughness arising from a brittle–ductile laminate architecture at the millimeter scale are fabricated and investigated. Such a hierarchical toughening approach increases the dissipated energy by more than 30‐fold during fracture with minimal loss in stiffness and strength. Using simple energy balance arguments and fracture mechanics concepts, guidelines are established for the design of nacre‐like composites with a remarkable combination of stiffness, strength, and toughness. This demonstrates the possibility to controllably introduce toughening mechanisms at different length scales and to thus fabricate hierarchical composites with high fracture resistance in spite of the brittle nature of their main inorganic constituents. Abstract : The design principles of tough biological materials are investigated by studying nacre‐inspired composites structured across three length scales. The organic layers between nacre layers are conceptually mimicked using polymer films in between synthetic nacre. These hierarchical materials exhibit high mechanical properties and offer new insights into the multiscale toughening mechanisms responsible for the outstanding fracture resistance of mollusk shells.